INTENSI MAHASISWA YOGYAKARTA BERWIRAUSAHA BERBASIS TEKNOLOGI INFORMASI (TI) - Heru Kurnianto Tjahjono; Tri Maryati; Fauziyah Fauziyah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2013)
AbstractThe purpose of this study is to investigate intention to be entrepreneur among university students in Yogyakarta. Based on modification of TPB (theory of planned behavior) and TAM (technology acceptance model), this research specifically examined whether entrepreneur’s personality is an important antecedent to explain attitude, risk perception and subjective norm of entrepreneur based on information technology (IT). This research tested whether attitude, risk perception and subjective norm of entrepreneur based on IT are important predictors to explain students’ intention to become entrepreneur based on IT. This research is a replication model proposed by Tjahjono and Palupi (2014). The samples in this research were 300 students from four large universities in Yogyakarta with purposive technique and were analyzed using structural equation modeling (SEM). The results of this research showed that attitude, risk perception, and subjective norm are consequences of entrepreneur’s personality and at the same time as antecedents to explain students’ intentions to be entrepreneur based on IT.Keywords: TPB, TAM and students intention to be entrepreneur.AbstrakPenelitian ini bertujuan untuk menginvestigasi intensi mahasiswa di Yogyakarta berwirausaha. Berbasis pada modifikasi TPB (theory of planned behavior) dan TAM (technology acceptance model), penelitian ini secara spesifik menguji apakah kepribadian berwirausaha merupakan anteseden penting dalam menjelaskan sikap, persepsi resiko dan norma subjektif berwirausaha yang berbasis TI. Selanjutnya apakah sikap, persepsi resiko dan norma subjektif berwirausaha berbasis TI adalah prediktor penting dalam menjelaskan intensi mahasiswa berwirausaha yang berbasis TI. Penelitian ini merupakan replikasi model yang diajukan Tjahjono dan Palupi (2014). Sampel dalam penelitian ini adalah 300 mahasiswa 4 perguruan tinggi besar di Yogyakarta dengan teknik penyampelan secara purposive. Penelitian ini dianalisis dengan menggunakan SEM. Hasil penelitian menunjukkan bahwa sikap, persepsi resiko dan norma subjektif berwirausaha berbasis TI adalah konsekuensi kepribadian berwirausaha sekaligus anteseden intensi berwirausaha berbasis TI.Kata kunci: TPB, TAM dan intensi mahasiswa berwirausaha.